Hubungan Pendidikan dan Umur Ibu dengan Pemantauan Tumbuh Kembang Balita di Wilayah Kerja Puskesmas Banjar Bangkalan - Ainur Risalah; Euvanggelia Dwilda Ferdinandus; Budi Utomo; Bagus Setyoboedi (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Growth monitoring achievements in Indonesia are still low, including in Bangkalan District, which ranks lowest in East Java, while the Banjar Bangkalan Community Health Center only recorded 2.34% of toddlers, or 22 toddlers, suffering from malnutrition. Low monitoring rates may be related to factors such as the mother's education and age, which affect knowledge, psychological readiness, and parenting practices. To date, there has been no research in Bangkalan analyzing the relationship between these two factors and growth monitoring based on Minister of Health Regulation No. 6 of 2024. This study used a quantitative cross-sectional design on 43 mothers with consecutive sampling, where data were collected through data collection sheets and analyzed using Fisher's Exact test. The results showed that most mothers had higher education (67.4%) and were aged ≥20 years (81.4%), but 65.1% did not monitor growth and development according to the standards. There was a weak positive relationship between education (p = 0.015) and maternal age (p = 0.036) with growth and development monitoring. These findings indicate a weak positive correlation between education and maternal age with growth monitoring of toddlers in the Banjar Bangkalan Community Health Center Working Area, making it important to provide assistance to mothers with low education and age 20 years so that growth monitoring of toddlers can be carried out optimally. Keywords: Maternal Education, Maternal Age, Growth Monitoring of Toddlers.  ABSTRAK Capaian pemantauan tumbuh kembang di Indonesia masih rendah, termasuk di Kabupaten Bangkalan yang menempati posisi terendah di Jawa Timur, sementara Puskesmas Banjar Bangkalan hanya mencatat 2,34% balita dengan jumlah 22 balita yang mengalami gizi buruk. Rendahnya pemantauan dapat berkaitan dengan faktor pendidikan dan umur ibu, yang memengaruhi pengetahuan, kesiapan psikologis, serta praktik pengasuhan. Hingga saat ini, belum terdapat penelitian di Bangkalan yang menganalisis hubungan kedua faktor tersebut terhadap pemantauan tumbuh kembang berdasarkan Permenkes No. 6 Tahun 2024. Penelitian ini menggunakan desain kuantitatif cross sectional pada 43 ibu dengan teknik consecutive sampling, di mana data dikumpulkan melalui lembar pengumpulan data dan dianalisis menggunakan uji Fisher’s Exact. Hasil penelitian menunjukkan bahwa sebagian besar ibu memiliki pendidikan tinggi (67,4%) dan umur ≥20 tahun (81,4%), namun 65,1% tidak melakukan pemantauan tumbuh kembang sesuai standar. Terdapat hubungan positif lemah antara pendidikan (p = 0,015) dan umur ibu (p = 0,036) dengan pemantauan tumbuh kembang. Hal ini menandakan adanya hubungan positif lemah antara pendidikan dan umur ibu dengan pemantauan tumbuh kembang balita di Wilayah Kerja Puskesmas Banjar Bangkalan, sehingga penting memberikan pendampingan kepada ibu dengan pendidikan rendah dan umur 20 tahun agar pemantauan tumbuh kembang balita dapat berjalan secara optimal.  Kata Kunci: Pendidikan Ibu, Umur Ibu, Pemantauan Tumbuh Kembang Balita.